Nutrition policy in Burkina Faso - Vanderkooy, A.; Verstraeten, Roosmarijn; Becquey, Elodie; Diatta, Ampa Dogui; Buttarelli, E.; Diop, Loty; Touré, Mariama (International Food Policy Research Institute, 2019)
This brief summarizes nutrition-relevant policies in Burkina Faso. We examine i) nutrition context, policy objectives, indicators, budget, and activities, ii) key beneficiaries, actors and coordination, iii) monitoring, evaluation, and accountability, and iv) whether current policies are aligned with the World Health Assembly (WHA) global targets.